PENGARUH MEDIA SOSIAL TERHADAP KESEHATAN MENTAL GENERASI Z: MENELITI DAMPAK KETERGANTUNGAN DIGITAL - Nabila Hani Puspita Bhakti; Khodijah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the impact of social media addiction on the mental health of Generation Z. Generation Z, consisting of individuals born between 1997 and 2012, is a cohort that grew up in the digital era and is highly connected to various social media platforms. Although social media offers various benefits, such as connectivity and access to information, excessive addiction can lead to various mental health problems, including anxiety, depression, and low self-esteem. Through surveys and in-depth interviews with respondents from various backgrounds, this study identified patterns of social media use and its impact on psychological well-being. The results showed that there was a significant relationship between time spent on social media and increased negative mental health symptoms. This study provides important insights for parents, educators, and policymakers to understand the risks associated with social media use among Generation Z and encourage healthier usage practices and interventions needed to support their mental health.